Coated Diammonium Phosphate Combined With Humic Acid Improves Soil Phosphorus Availability and Photosynthesis and the Yield of Maize - Chen, Qi; Qu, Zhaoming; Li, Zeli; Zhang, Zixin; Ma, Guohua; Liu, Zhiguang; Wang, Yanfeng; Wu, Liang; Fang, Fuli; Wei, Zhanbo; Zhang, Min (Frontiers in Plant Science, 2021)
Controlled release phosphorus (P) fertilizers and Humic acid (HA) applications are two effective and significant techniques measures for preventing P loss and enhancing maize development. However, the underlying physiological mechanism of how the controlled release P fertilizers combined with HA affect the maize production and P use efficiency (PUE) remains unknown. The effects of applying coated diammonium phosphate (CDAP) and HA together on soil nutrient supply intensity, soil phosphatase activity, the photosynthesis, endogenous hormone contents, and yield of maize, as well as PUE, were examined in this study. In a pot experiment, two types of P fertilizer–CDAP and diammonium phosphate (DAP)–were utilized, as well as two FA application rates (0 and 45 kg ha-1) and two P levels (60 and 75 kg P2O5 ha-1). Results showed that the key influencing elements of maize growth and yield were soil available P content and plant photosynthesis and hormone levels. The combination of CDAP and HA had a greater impact on yield and PUE over the course of two years than either DAP alone or DAP combined with HA. Besides, using CDAP in combination with HA increased the yield and PUE by 4.2% and 8.4%, respectively, as compared to the application of CDAP alone at 75 kg P2O5 ha-1. From the twelve-leaf to milk stages, soil available P content was increased by an average of 38.6% with the combination of CDAP and HA compared with the application of CDAP alone at 75 kg P2O5 ha-1. In addition, the application of CDAP combined with HA boosted the activities of ATP synthase, as well as the content of cytokinin, and hence improved the maize photosynthetic rate (Pn). When compared to the application of CDAP alone or DAP combined with HA, the Pn of CDAP+HA treatments was enhanced by 17.9%-35.1% at the same P rate. In conclusion, as an environmentally friendly fertilizer, the combined application of CDAP and HA improved soil nutrient supply intensity, regulated photosynthetic capabilities, and increased the yield and PUE, which is important for agricultural production, P resource conservation, and environmental protection.